Preparatory alpha-band oscillations reflect spatial gating independently of predictions regarding target identity - Wildegger, T; van Ede, F; Woolrich, M; Gillebert, C; Nobre, A (American Physiological Society, 2017)
Preparatory modulations of cortical alpha-band oscillations are a reliable index of the voluntary allocation of covert spatial attention. It is currently unclear whether attentional cues containing information about a target's identity (such as its visual orientation), in addition to its location, might additionally shape preparatory alpha modulations. Here, we explore this question by directly comparing spatial and feature-based attention in the same visual detection task while recording brain activity using magneto-encephalography (MEG). At the behavioural level, preparatory feature-based and spatial attention cues both improved performance, and did so independently of each other. Using MEG, we replicated robust alpha lateralisation following spatial cues: in preparation for a visual target, alpha power decreased contralaterally, and increased ipsilaterally to the attended location. Critically, however, preparatory alpha lateralisation was not significantly modulated by predictions regarding target identity, as carried via the behaviourally effective feature-based attention cues. Furthermore, non-lateralised alpha power during the cue-target interval did not differentiate between uninformative cues and cues carrying feature-based predictions either. Based on these results we propose that preparatory alpha modulations play a role in the gating of information between spatially segregated cortical regions, and are therefore particularly well suited for spatial gating of information.